Anti-corruption management in a government institution as an element of anti-corruption policy in Ukraine - Rumiantseva, Daryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
It is noted that the increase in corruption crimes among employees of public institutions requires changes in approaches to anti-corruption policy in the management of the organization. It has been announced that it is expedient for anti-corruption management to enter state bodies in accordance with the state anti-corruption policy, using corruption risks, increasing public confidence in state bodies, and being implemented in various state bodies taking into account the specifics of each. Given the high urgency of the issue for Ukraine, there is a lack of scientific work to determine the best ways to solve problem situations. The purpose of the article is to analyze anti-corruption management in a public institution as one of the components of anti-corruption policy in Ukraine. Anti-corruption management is described as an element of strategic planning. It`s role in the formation of a positive image, a strong business reputation of the state institution is considered. The directions of realization of the anti-corruption management system are presented. The interpretation of the concepts of «management» and «anti-corruption management» is presented. The tasks of anti-corruption management are listed and characterized. The importance of implementing the provisions of the anti-corruption management program for the development of corporate culture is described. The destructive phenomenon in anti-corruption management is considered – «frustrating tolerance», which negatively affects the formation of an effective management strategy. The importance of identifying corruption risks when planning anti-corruption measures is noted. The key aspects that need to be taken into account when identifying corruption risks in the organizational and managerial activities of a public institution are considered. The list of documents, the maintenance of which is necessary within the framework of anti-corruption management, is noted. The expediency of observing certain stages of the fight against corruption, taking into account the specifics of the public sector, is outlined. The system of compliance and its content are characterized as one of the most effective approaches to the implementation of anti-corruption management. The principles on which each of the groups of anti-corruption measures should be based are indicated. Emphasis is placed on the expediency of focusing anti-corruption management on the formation of a conscious attitude of each employee of a state institution to good behavior, quality and transparency of work, its governing bodies and the activities of its employees. A meaningful description of the content of the implementation of anti-corruption policy in personnel management through the prism of the formation of a negative attitude to corruption, training and implementation of measures to disseminate information on anti-corruption programs, includes the following system of measures. Options for organizing training and exchange of experience among employees of government agencies on the prevention of corruption in the performance of professional duties are considered. In conclusion, it should be noted that the issue of quality anti-corruption management for Ukrainian government agencies is a priority issue and requires the development of a system of effective measures taking into account the specifics of each sector.